Policy Evaluation of Accelerated Vat Refund on Export (Case Study on Indonesian Large Tax Office 1) - Franki Nababan; Titi Muswati Putranti; Mohamad Luhur Hambali (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims are to analyze the tax administration on the policy of accelerated VAT refund on exports and to analyze the evaluation of the policy for accelerated VAT refund on exports at Indonesian Large Tax Office 1 (LTO 1). The research method used is qualitative research with data collection techniques through in-depth interviews with Indonesian tax stakeholders and literature studies. The results of this study were found that the accelerated VAT refund, especially during the COVID-19 pandemic, can help the cash flow of the Taxable Entrepreneur (TE) to be used to support their business, the process of implementing the accelerated VAT refund policy is not yet effective, as is in line with the findings of the Audit Board of the Republic of Indonesia (Badan Pemeriksa Keuangan Republik Indonesia / BPK RI), which found that the completion of the VAT Refund process that exceeds the time period, and there are also administrative technical obstacles that must be corrected in order to improve services to TE. Some way that can be used is to simplify the bureaucracy, through a reorganization of the organizational section related to the preliminary VAT refund and optimizing the use of technology in the administration of the accelerated VAT refund.